DEVELOPMENT OF STUDENT WORKSHEET BY USING CONTEXTUAL TEACHING AND LEARNING APPROACH ON SUBJECT MATTER OF LINEAR PROGRAM FOR STUDENTS OF SMK CLASS X - Fitria Rahmawati; Uus Kusdinar (Universitas Ahmad Dahlan, 2018)
The learning process that still tends to teacher-centered makes the students less active in the learning process. The use of teaching materials still less facilitates students in the process of learning mathematics. This research aims to develop and test the feasibility of the Student Work Sheet with Contextual Teaching and Learning (CTL) approach to the subject matter of linear program for students of SMK class X. The research of Student Work Sheet development with Contextual Teaching and Learning (CTL) approach to the subject matter of linear program for students of SMK class X follow the steps of Research and Development (R & D) covering: (1) potential and problem, (2) data collection, 3) product design, (4) product validation, (5) design revision, (6) product trial, (7) product revision, (8) trial use, (9) revision of the final product. Research subjects are material experts, media experts, and students of class X SMK. Data analysis using qualitative and quantitative descriptive analysis. Product assessment results by a material expert, media expert, and student responses are included in the excellent category. The results showed that the Student Work Sheet with Contextual Teaching and Learning (CTL) approach to the subject matter of linear program for students of SMK class X is feasible to be used in the learning process.